Teacher Strategy Management in Implementing P5RA in the Independent Curriculum in Islamic Junior High Schools: Manajemen Strategi Guru Dalam Menerapkan P5RA Pada Kurikulum Merdeka Di Madrasah Tsanawiyah - Basuki; Ahd. Mujahid (Fakultas Tarbiyah Dan Ilmu Keguruan Institut Agama Islam An-Nawawi Purworejo, 2025)
Strategy refers to a method or systematic plan that serves as a general guideline for action in order to achieve predetermined objectives. In the context of learning, strategy is closely related to the approaches and techniques employed by teachers in delivering instructional content within a specific learning environment. This study was conducted at MTs Negeri 2 Kepulauan Meranti using a qualitative research approach. The aim of this research was to analyze teacher strategies, as well as the supporting and inhibiting factors in the implementation of the Rahmatan lil ‘Alamin Student Profile (P5RA) within the Merdeka Curriculum. The findings indicate that the implementation of teacher strategies in applying the Rahmatan lil ‘Alamin Student Profile within the Merdeka Curriculum has not yet been fully optimal, particularly in terms of communication and instructional delivery methods. The strategies employed by teachers include the internalization of values such as civility (ta’addub), role modeling (qudwah), brotherhood (muwathanah), moderation (tawassuth), balance (tawazun), justice (i‘tidal and musawah), deliberation (shura), tolerance (tasamuh), as well as development (tathawwur) and innovation (ibtikar). These values are integrated into classroom instruction and P5RA project-based activities to foster students’ character development in line with the principles of moderation and moral integrity. Furthermore, the supporting factors in the implementation of the Rahmatan lil ‘Alamin Student Profile include the strong commitment of the school principal and teaching staff to the execution of P5RA, collaborative partnerships between teachers and parents, and the organization of professional development activities such as workshops and seminars related to the Merdeka Curriculum. Conversely, the inhibiting factors identified consist of insufficient parental and teacher supervision, as well as the limited availability of comprehensive training and workshops specifically focused on the implementation of the Merdeka Curriculum and P5RA. These findings suggest that strengthening teacher strategies and institutional support is essential to optimize the implementation of the Rahmatan lil ‘Alamin Student Profile in madrasah settings.